Relevansi Doktrin Trinitas dalam Menganalisis Budaya : Kontribusi Pemikiran Lesslie Newbigin dan Johan Herman Bavinck - Doni Herwanto Harianja (Societas Dei: Jurnal Agama dan Masyarakat, 2023)
This article examines the theology of culture from the perspective of Lesslie Newbigin and Johan Herman Bavinck. It is argued that the Trinitarian framework is appropriate for reading and analyzing culture. By comparing these two figures, the author shows the application of the Trinitarian framework in reading and analyzing the culture in Newbigin and Bavinck's thinking. From this study, the author shows the diversity of the theology of cultures from the Reformed theological tradition, which can be applied mainly in the life of a pluralistic society.